Trajectories of abstinence-induced Internet gaming withdrawal symptoms: A prospective pilot study - Kaptsis, Dean (Addict Behav Rep, 2016)
Internet Gaming Disorder (IGD) is positioned in the appendix of the DSM-5 as a condition requiring further study. The IGD criteria refer to withdrawal symptoms, including irritability, anxiety, or sadness, that follow cessation of Internet gaming (APA, 2013). The aim of this study was to prospectively examine the nature of Internet gaming withdrawal symptoms, if they occur, under gaming abstinence conditions. This study employed a repeated-measures protocol to examine the cognitive-affective reactions of participants undertaking an 84-h Internet gaming abstinence period. The sample included individuals who met the IGD criteria as well as those who regularly played Internet games but did not meet the IGD criteria. Outcome variables included affect (positive and negative), psychological distress (depression, anxiety, stress), and Internet gaming withdrawal symptoms (craving/urge, thoughts about gaming, inability to resist gaming). A total of 24 participants (M(age) = 24.6 years, SD = 5.8) were recruited from online gaming communities, and completed a series of online surveys before, during, and after abstaining from Massively Multiplayer Online (MMO) games. Both the IGD group and the non-IGD group experienced an abstinence-induced decline in withdrawal symptomatology, negative affect, and psychological distress. The IGD group experienced its largest decline in withdrawal symptomatology within the first 24 h of abstinence. These preliminary data suggest that gaming withdrawal symptoms may follow, at least initially, negative linear and quadratic trends. Further prospective work in larger samples involving longer periods of abstinence is required to verify and expand upon these observations.